Thermodynamic, exergy and exergo-environmental analysis of waste feedstock for the H2 production: A simulation study - Bilal Kazmi; Syed Ali Ammar Taqvi; Usama Ahmed; Libor Štěpanec; Salman Raza Naqvi (Energy Conversion and Management: X)
The aim of the present work was to study the feasibility of a sustainable thermochemical pathway to produce hydrogen by co-gasifying oily sludge waste (OSW), municipal solid waste (MSW) and plastic waste in steam-assisted reforming along with the use of CaO as a CO2 sorbent. A simulation-based parametric analysis was performed to optimize three key process variables: reactor temperature (650–800 °C), steam-to-biomass ratio (0.88–2.22), and CaO-to-biomass ratio (1.77–2.22).. The maximum Hydrogen yield of 95.9 % was achieved at 800 °C using pure OSW, indicating high conversion efficiency. Among the feedstock blending scenarios, Case IV (90 % MSW / 10 % OSW) demonstrated the lowest exergy destruction (414.02  kW) and a favorable environmental destruction index (0.719), indicating high process sustainability. In contrast, Case I showed the highest exergy loss (1589.14  kW), mainly attributed to uneven energy distribution and tar formation. The results highlight the importance of the composition of feedstock and the operating conditions which play a critical role in enhancing efficiency of the process. In general, the given approach can support efficient valorization of waste and generation of clean hydrogen, contributing to the targets on the way to a decarbonized economy and circle-economy.